Abdi Dalem Keraton Yogyakarta in the perception of Generation Z - Sari, Wulan Purnama; Bajari, Atwar; Hafiar, Hanny; Lestari, Puji (Universitas Padjadjaran, 2023)
Background: The Abdi Dalem Keraton Yogyakarta is a state apparatus that has dedicated his life to the Palace and has a role as an agent for preserving culture, especially Javanese culture. This is manifested in the way they communicate and also the way the Abdi Dalem dress. The actions taken by the Abdi Dalem reflect that they are living examples of Javanese culture, and it is their duty as agents to preserve it. Abdi Dalem is often perceived as being attached to something traditional or old-fashioned. Purpose: The research was conducted to analyze and describe the perceptions of Generation Z about the Royal Palace Servants of Yogyakarta. Generation Z was chosen because this generation is known as the digital generation and has main characteristics in terms of mastery over technology and information, making this generation very close to the digital world, and then how the digital generation perceives or sees Abdi Dalem, who are traditional and far from digitalism. Methods: This study uses a quantitative approach and survey methods. Data was collected using a questionnaire, with the response being Generation Z, who live in the Yogyakarta area. Conclusion: Based on the stages of forming perceptions starting from stimulation, organizing, interpreting-evaluating, storing, and recalling. The results of the study show that the formation of Generation Z’s perception of Abdi Dalem is limited to people who work at the Palace, the Yogyakarta Palace reminds Generation Z of Abdi Dalem but not Javanese culture. The language and clothing of the Abdi Dalem also do not stimulate the perceptions of Generation Z, nor do the media stimulate the formation of Generation Z’s perceptions. Implication: Generation Z’s perception of Abdi Dalem is minimal because the topic of Abdi Dalem is not the main topic, especially in their information search system on social media. This condition limits the actions and ways of communicating from Generation Z regarding Abdi Dalem.culture, and c) and to inform the young generation about local customs and culture.